Analisis Implementasi Good Corporate Governance (GCG) (Kasus Pada PT Industri Telekomunikasi Indonesia (persero)) - Kesumah, Henri Ferangadita (Program Studi Manajemen, 2021)
Good Corporate Governance (GCG) in Indonesia is still low. Although currently BUMNs are competing to implement GCG, this is only limited to fulfilling business sequences. In reality, the system of governance has not been implemented optimally. Companies carrying out GCG practices are still limited to compliance with various regulations. PT INTI (Persero) is one of the BUMNs that has implemented GCG principles since 2012. However, in practice, there are still many obstacles that indicate that the implementation of GCG is not running properly. The phenomenon that occurred included the appointment of a suspect in the President Director of PT INTI (Persero) by the KPK in the procurement of the Baggage Handling System work at PT Angkasa Pura Propertindo which was carried out by PT Industri Telekomunikasi Indonesia (Persero) in 2019. The results showed that PT INTI (Persero) has implemented GCG implementation practices in accordance with applicable regulations. With a value of 79.705, it means that the quality of GCG implementation at PT INTI (Persero) is at a vulnerable value of 75 to 85 which is included in the